The Impact of Career Development, Remuneration, Work Motivation, and Organizational Commitment on Job Satisfaction - Halimatusha'diah Halimatusha’diah; Bibin Rubini; Hendarman Hendarman (CV. Creative Tugu Pena, 2026)
This study aims to test the hypothesis of direct and indirect relationships between the research variables—career development, compensation, work motivation and organisational commitment—and job satisfaction. The research method employed a quantitative study, with the sample size calculated using Taro Yamane’s formula, resulting in a sample of 114 P3K teachers teaching at state senior secondary schools in Karawang Regency. The instruments used in this study comprised questionnaires for each research variable, which had previously undergone validation. Data were analysed using SPSS to test the hypotheses regarding direct and indirect effects. However, prior to hypothesis testing, the prerequisites for data analysis were assessed, namely the normality test, the homogeneity test and the linearity test. The results of the study indicate that there were four direct effects for which the hypotheses were accepted and three direct effects for which the hypotheses were rejected. Regarding indirect effects, two hypotheses were accepted and one hypothesis was rejected. The findings of this study indicate that improvements in career development, remuneration, work motivation and organisational commitment play a role in enhancing teachers’ job satisfaction, particularly amongst P3K-status teachers at state senior secondary schools in Karawang Regency